Osseointegrated Oral implants Mechanisms of Implant Anchorage, Threats and Long-Term Survival Rates - Albrektsson, Tomas (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
In the past, osseointegration was regarded to be a mode of implant anchorage that simulated a simple wound healing phenomenon. Today, we have evidence that osseointegration is, in fact, a foreign body reaction that involves an immunologically derived bony demarcation of an implant to shield it off from the tissues. Marginal bone resorption around an oral implant cannot be properly understood without realizing the foreign body nature of the implant itself. Whereas the immunological response as such is positive for implant longevity, adverse immunological reactions may cause marginal bone loss in combination with combined factors. Combined factors include the hardware, clinical handling as well as patient characteristics that, even if each one of these factors only produce subliminal trauma, when acting together they may result in loss of marginal bone. The role of bacteria in the process of marginal bone loss is smaller than previously believed due to combined defense mechanisms of inflammation and immunological reactions, but if the defense is failing we may see bacterially induced marginal bone loss as well. However, problems with loss of marginal bone threatening implant survival remains relatively uncommon; we have today 10 years of clinical documentation of five different types of implant displaying a failure rate in the range of only 1 to 4 %.